2017
DOI: 10.1007/s11280-017-0491-8
|View full text |Cite
|
Sign up to set email alerts
|

An effective approach for the protection of privacy text data in the CloudDB

Abstract: Due to the advantages of pay-on-demand, expand-on-demand and high availability, cloud databases (CloudDB) have been widely used in information systems. However, since a CloudDB is distributed on an untrusted cloud side, it is an important problem how to effectively protect massive private information in the CloudDB. Although traditional security strategies (such as identity authentication and access control) can prevent illegal users from accessing unauthorized data, they cannot prevent internal users at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Methods that implement queryable encrypted databases on string data types need to support LIKE operator to search on encrypted data. These methods can be considered in three categories: based on Bloom filter [22], [23], based on mapping [24], [25] and converting string to number [26], [27].…”
Section: String Data Typementioning
confidence: 99%
“…Methods that implement queryable encrypted databases on string data types need to support LIKE operator to search on encrypted data. These methods can be considered in three categories: based on Bloom filter [22], [23], based on mapping [24], [25] and converting string to number [26], [27].…”
Section: String Data Typementioning
confidence: 99%
“…Wu et al [1] observed the encryption technique to prevent understanding of user data. Before applying the query on the user data, it should be decrypted first and after finishing the query process, the data is again encrypted.…”
Section: Related Workmentioning
confidence: 99%
“…The users can store, modify and retrieve the data anywhere in the world. Therefore, it is essential to secure privacy in a cloud databases [1]. According to the Information security breaches survey (ISBS), 2015 large organizations stated that there was an element 81% of staff involved in some of the breaches they suffered [2], 90% of organizations feel vulnerable to an insider threat according to the Insider Threat 2018 Report [3] and Forrester Research [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers also attempt to study the problem from the view of technologies, e.g. by using encryption (Wu et al, 2017), identity authentication (Han et al, 2016) and authorization and access control (Shao et al, 2014;Li et al, 2015). However, most of the existing methods are designed only for users' data privacy, so are not practicable for users' behavior privacy.…”
Section: Problem Statement 21 Literature Reviewmentioning
confidence: 99%